Tatbiq Thoriqoh al Insya’ al Muwajjah Li Tahsin Mahārah al Kitābah Fi Ta’lim al Lughah al ‘Arabiyyah Bi Madrasah al Tsānawiyah al Islamiyyah “ Ar Rahmān “ Sumoyono , Jombang - Fauziyah, Naily; Qomariyah, Lailatul (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2024)
Writing skills are one of the language skills taught to students in learning Arabic. The Insha' al Muwajjah method is a support for understanding writing skills in Arabic. The aims of this research are (1) to determine the application of the insya' al Muwajjah method to improve writing skills in Arabic language learning in class writing in Arabic language learning in class XI MA Ar-Rahman Sumoyono Jombang. This research uses qualitative research with a descriptive approach. Data obtained using Observation, Interview and Documentation methods. From the results of observations carried out by researchers, the Insya' al Muwajjah method applied at MA Ar-Rahman Sumoyono Jombang uses the insya' al muwajjah narrative or story method. The supporting and inhibiting factors from the research results are Supporting Factors (1) qualified teachers (2) methods that are easy to understand (3) teaching materials that meet the requirements in the learning process (3) high enthusiasm of the students. Inhibiting Factors (1) students' different backgrounds (2) students' ability to memorize vocabulary often experiences difficulties because each student has a different absorption capacity, (3) lack of use of additional media (4) creativity of some students is not optimal in processing vocabulary into a sentence Keyword : Insha' al-Muwajjah, Arabic Language Learning, Maharah Kitabah